Photosynthetic Characteristics and Uptake and Translocation of Nitrogen in Peanut in a Wheat–Peanut Rotation System Under Different Fertilizer Management Regimes - Liu, Zhaoxin; Gao, Fang; Yang, Jianqun; Zhen, Xiaoyu; Li, Ying; Zhao, Jihao; Li, Jinrong; Qian, Bichang; Yang, Dongqing; Li, Xiangdong (Frontiers in Plant Science, 2019)
Better management of N fertilizer is essential for improving crop productivity. Wheat (Triticum aestivum L.)–peanut (Arachis hypogaea L.) relay intercropping rotation systems are a mainstay of the measures to improve the economic and food security situation in China. Therefore, a 2-year field study (2015–2017) was conducted to evaluate the effect of different N fertilizer management regimes on the photosynthetic characteristics and uptake and translocation of N in peanut in the wheat–peanut rotation system. We used common compound fertilizer (CCF) and controlled-release compound fertilizer (CRF) at the same N–P2O5–K2O proportion (The contents of N, P2O5, and K2O in the two kinds of fertilizer were 20, 15, and 10%, respectively.). The fertilizer was applied on the day before sowing, at the jointing stage or the flag leaf stage of winter wheat, and at the initial flowering stage of peanut in various proportions, with 0 kg N ha-1 as the control. Results showed that split applications of N significantly increased leaf area index (LAI) and chlorophyll content and improved photosynthetic rate, thus increasing the pod yield of peanut. Topdressing N at the jointing stage (S1) or at the flag leaf stage of wheat (S2) and supplying part of the N at the initial flowering stage of peanut increased pod yield. Withholding N until the flag leaf stage (S2) did not negatively affect wheat grain yield; however, it increased N accumulation in each organ and N allocation proportions in the peanut pod, ultimately improving pod yield. With the same N–P2O5–K2O proportion and equivalent amounts of nutrient, CRF can decreased malondialdehyde (MDA) and maintain a relatively high LAI and chlorophyll content at the late growth stage of peanut, prolong the functional period of peanut leaves and delay leaf senescence, resulting in an increase of pod yield over that with CCF. At S1, CRF resulted in a better pod yield than CCF by 9.4%, and at S2 it was 12.6% higher. In summary, applying N fertilizer in three splits and delaying the topdressing fertilization until the flag leaf stage of winter wheat increases total grain yields of wheat and peanut. This method could therefore be an appropriate N management strategy for wheat–peanut relay intercropping rotation systems in China.